Clinical features of prostate-specific antigen bounce after 125I brachytherapy for prostate cancer. (30th July 2018) - Kubo, Katsumaro; Wadasaki, Koichi; Kimura, Tomoki; Murakami, Yuji; Kajiwara, Mitsuru; Teishima, Jun; Matsubara, Akio; Nagata, Yasushi
Abstract: The aim of this study was to analyse the clinical features of prostate-specific antigen (PSA) bounce and the difference between biochemical failure and large-magnitude PSA bounce. The cases of 352 patients with prostate cancer who underwent brachytherapy were analysed. PSA bounce was defined as an increase in PSA of ≥0.2 ng/ml above an initial PSA nadir, with subsequent decline to or below that initial nadir without treatment. PSA bounce +2 was defined as an increase in PSA of ≥2.0 ng/ml above the nadir with subsequent decline to or below that initial nadir without treatment. We analysed the rates, time to onset, and predictive factors for PSA bounce and PSA bounce +2. The median follow-up period at the time of evaluation was 82 months. One hundred and seventeen patients had PSA bounce; of them, 10 had PSA bounce +2. Biochemical failure occurred in 29 patients. The median times to onset of PSA bounce, PSA bounce +2, and biochemical failure were 20, 17.5 and 51 months, respectively. Younger age at implant and larger prostate volume were significant predictive factors for PSA bounce. Age was a significant factor for PSA bounce +2, and PSA bounce +2 patients were significantly younger than biochemical failure patients. The maximum duration from the date of PSA bounce +2 to the date when PSA level decreased was 12 months. Age at implant, time to onset, and 1-year follow-up after an increase in PSA level of ≥2 ng/ml above nadir level are useful for distinguishing between biochemical failure and PSA bounce +2.